CGSpace training Manual - Ramírez, Margarita M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
CGSpace is an online repository of agricultural research outputs and results produced by different parts of CGIAR and partners. It takes the form of a website managed by ILRI, and contains 20 communities for different centers and CRPs. CGSpace is built using an open-source software called DSpace.3